Inheritance of bruchid resistance in cowpea - Adjadi, O.; Singh, B.B.; Singh, S.R. (1985)
This study was undertaken to elucidate the nature of inheritance of resistance to bruchids [Callosobruchus maculatus. (F.)] in cowpea [Vigna unguiculata (L.) Walp.]. The parental F1, F2, and backcross populations involving three resistant and two susceptible parents were bioassayed in the laboratory for bruchid reaction on an individual plant basis. The reaction of F1 seeds was similar to that of seeds from the maternal parent, indicating that the genotype of the maternal plant controls bruchid infestation. The F2 seeds derived from F1 plants represented the true hybrid population and the mean adult emergence was similar to that of the susceptible parents, indicating complete dominance of susceptibility. No reciprocal differences were observed. The F2 plants derived from the six crosses segregated into a ratio of 15 susceptible:l resistant, indicating digenic inheritance. These results were further supported by the backcross data. The Fl plants from the backcross involving the resistant parent segregated into a 3 susceptible:l resistant ratio, whereas those involving the susceptible parent were uniformly susceptible. These data indicate that resistance to bruchids in cowpea is controlled by two recessive genes for which symbols rcml and rcm2 are being proposed.